A new species of Anthurium (Araceae) from Minas Gerais State, Southeastern Brazil - Gonçalves, Eduardo G.; Paula, Luiza F. A. De (Phytotaxa, 2016)
A new species of Anthurium (A. mucuri E.G.Gonç. & L.F.A. de Paula) is described and illustrated. It occurs in rocky outcrops (inselbergs) in Minas Gerais state, Southeastern Brazil and it is so far know from a restricted area around the city of Teófilo Otoni. It seems to be closer to Anthurium viridispathum E.G.Gonç., but differs mainly in having smaller overall dimensions, a much narrower leaf blade and spathe and for the spathe that is glaucous in the inner surface. Anthurium mucuri is placed in the section Urospadix Engl. subsection Obscureviridia Engl.